Anomali PBV dan Peran Profitabilitas dalam Menentukan Harga Saham LQ45: Studi 2021–2023 - Prasetiyo, Tegar; Bakaruddin, Bakaruddin; Hastuti, Dwi (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Muhammadiyah Riau, 2025)
This study aims to examine how Price to Book Value (PBV), profit level, and dividend policy affect the stock prices of companies listed in the LQ45 index on the Indonesia Stock Exchange during the period 2021 to 2023. This study uses quantitative methods with secondary data obtained through financial reports from 22 companies that are consistently included in the LQ45 index during the period studied. The results show that PBV has a significant negative impact on stock prices, while profitability has a significant positive impact. Dividend policy, on the other hand, showed no significant effect. Overall, these three variables simultaneously affect stock prices. This study provides a new perspective on the dynamics of company performance in the LQ45 index, emphasizing the importance of profitability as a key factor in investment decisions in the capital market.